2021
DOI: 10.1016/j.clinthera.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Omission of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers Is Associated With Morbidity and Mortality in Coronavirus Disease 2019

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The importance of statin withdrawal and its probable mechanisms of action were extensively reviewed in 2006 [ 181 ]. For COVID-19, similar findings have been published for ACE inhibitor and ARB withdrawal [ 164 , 165 , 166 , 167 , 168 ].…”
Section: Statin and Ace Inhibitor/arb Withdrawalsupporting
confidence: 71%
See 1 more Smart Citation
“…The importance of statin withdrawal and its probable mechanisms of action were extensively reviewed in 2006 [ 181 ]. For COVID-19, similar findings have been published for ACE inhibitor and ARB withdrawal [ 164 , 165 , 166 , 167 , 168 ].…”
Section: Statin and Ace Inhibitor/arb Withdrawalsupporting
confidence: 71%
“…A clinical trial of telmisartan (an ARB) has yielded similar results [ 162 ]. Moreover, continuation of ACE inhibitor/ARB outpatient treatment after hospitalization has beneficial effects on COVID-19 outcomes [ 163 ], whereas discontinuing treatment can be harmful [ 164 , 165 , 166 , 167 , 168 ]. Similarly, an increase in COVID-19 mortality has been observed following withdrawal of statin treatment [ 169 , 170 ].…”
Section: Treating the Host Response To Covid-19 With Inexpensive Gene...mentioning
confidence: 99%
“…Global healthcare, cardiology departments, and health authorities recommend continuing RAAS inhibitor treatment of COVID-19 patients because of their proven anti-hypertensive activity and lack of evidence towards of harm to affected patients [ 198 , 199 ]. Several retrospective studies also reported that ICU requirements and COVID-19 death rates were inversely related to ACEIs/ARBs treatment in hypertensive, non-hypertensive and elderly patients [ [200] , [201] , [202] , [203] ]. As there is conflicting evidence regarding the role of ACEIs/ARB in COVID-19 susceptibility and outcomes, further studies should be performed in this direction by considering multiple factors related to ACEIs/ARB-associated ACE2 expression and level of Angiotensin II in such patients with and without COVID-19 [ 204 ].…”
Section: Cellular and Molecular Mechanism Of Coronavirus Infection And Its Association With Cardiovascular Systemmentioning
confidence: 99%
“…Another retrospective study reported that the provision of ACEIs/ARBs in the intensive care unit (ICU) for COVID-19 elderly patients was associated with a marked reduction in the mortality rates ( Oddy et al, 2021 ).…”
Section: Aceis/arbs In Covid-19 Patientsmentioning
confidence: 99%